Editorial Essay: What Is Organizational Research For?. (June 2015) - Davis, Gerald F.
Organizational research is guided by standards of what journals will publish and what gets rewarded in scholarly careers. This system can promote novelty rather than truth and impact rather than coherence. The advent of big data, combined with our current system of scholarly career incentives, is likely to yield a high volume of novel papers with sophisticated econometrics and no obvious prospect of cumulative knowledge development. Moreover, changes in the world of organizations are not being met with changes in how and for whom organizational research is done. It is time for a dialogue on who and what organizational research is for and how that should shape our practice.